Effect of growing media, irrigation regime, fertigation and mulching on productivity of tomato (Lycopersicn esculentum) in naturally-ventilated polyhouses in hills* - KUMAR, MANISH; KOHLI, U K; GUPTA, S K (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2003 and 2004 at vegetable research farm of the University, Nauni for 2 years to see the effect of different agro-techniques especially growing media, irrigation regime, PNS and mulching it is found that Module- 1 comprising soil: compost: sand (2: 1 : 1) growing media at 20 kpa irrigation regime, Integrated Plant Nutrient System with 50 kg NPW ha as basal and fertigation with water soluble fertilizer polyfeed(l9: 19:19) @ 250 kg/ ha starting at third week after transplanting and black polythene mulch recorded the higher productivity of 9.20 kg/ m' and 11.40 kg/m2 in 2003 and 2004 respectively.